Benefits of Combined Therapies in Burn Lesions: Enzymatic Debridement and Other Modern Approaches—Our Clinical Experience - Angela Tecuceanu; Camelia Tamaş; Anca Sava; Ruxandra Vatavu; Andreea Mioara Avram; Iulia Olaru; Bogdan Mihnea Ciuntu; Irina Mihaela Abdulan; Roxana Ciuntu; Mihaela Corlade; Irina Mihaela Hreniuc Jemnoschi; Andreea Ludușanu; et al. (Life)
Background: In thermal injuries, enzymatic debridement is a viable option for treating partial- and full-thickness burns, allowing for rapid removal of damaged tissue with minimal bleeding and without sacrificing healthy dermis. Enzymatic debridement using Nexobrid® combined with negative wound pressure therapy (NWPT) appears to promote healing, as enzymatic debridement helps preserve healthy tissue integrity and epithelial reserves. We explored therapeutic alternatives following enzymatic debridement to assess healing outcomes and reduce reliance on skin grafts. Methods: 24 patients with deep or partially deep thermal burns on 5–40% of total body surface area (TBSA) underwent enzymatic debridement; then, half received NWPT and the other half were treated with topicals. Results: Enzymatic debridement effectively removed necrotic tissue and facilitated healing. Only three patients required skin grafts (<10% TBSA). Enzymatic debridement combined with NWPT expedited daily healing, reduced hospitalization days, and eliminated wound secretion, as confirmed by bacteriological examination. This approach was more effective compared to enzymatic debridement followed by topical treatments. Conclusions: Nexobrid® in combination with NWPT is a promising alternative to surgical treatment, improving healing, reducing the need for skin grafts, and alleviating pain associated with dressing changes. It may be particularly useful in extensive burns, where epithelial reserves are limited.